2020
DOI: 10.1186/s13104-020-05071-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the expression level of miR-9-5p and miR-192-5p in gastrointestinal cancer: introducing novel screening biomarkers for patients

Abstract: Objective: It has been indicated that there is a tight association between cancer and different factors, such as environment and genetics, including aberrantly expressed microRNAs. The crucial role of microRNAs in the regulation of diverse signaling pathways in gastrointestinal cancer has been established in several studies. In this study, we aimed to evaluate the expression of microRNA-9 and -192 in colon and gastric cancers. After extracting the RNA from tissues and serum samples of patients, suffering from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Previous study showed that hsa-miR-192 was a tumor suppressor. It could suppress cell proliferation, metastasis, and stemness and induce apoptosis in different cancer types [ 26 32 ]. But its function in CC remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that hsa-miR-192 was a tumor suppressor. It could suppress cell proliferation, metastasis, and stemness and induce apoptosis in different cancer types [ 26 32 ]. But its function in CC remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the metabolites produced by intestinal microflora can stimulate the expression of miR-192-5p, which subsequently inhibits the proliferation of colon cancer cells via the RhoA-ROCK-LIMK2 pathway ( Huang et al, 2020 ). A recent study by Tavakolian and coworkers demonstrated that the expression of miR-192-5p is significantly reduced in tissues of human gastric cancer, suggesting that miR-192-5p may play an important role in gastric cancer ( Tavakolian et al, 2020 ). Consistently, vital studies have indicated that miR-192-5p plays a role in the resistance of EC and gastric cancer to chemotherapy, which reverses cisplatin resistance by targeting ERCC3 and ERCC4 in gastric cancer lines ( Hummel et al, 2014 ; Xie et al, 2019 ).…”
Section: Mir-192-5p In Human Diseasesmentioning
confidence: 99%
“…In addition, the rescue by miR-9-5p inhibitor of the effect of ZNRD1-AS1 knockdown and the inhibition by the miR-9-5p binding-site mutant of the effect of ZNRD1-AS1 overexpression further demonstrated that ZNRD1-AS1 may act as a buffer for miR-9-5p. This hypothesis is further supported by the suppressive effect of miR-9-5p on the proliferation, migration, and invasion of gastric cancer cells [ 12 , 13 ]. However, the ZNRD1-AS1 sequence has many miRNA response elements, suggesting that ZNRD1-AS1 may play a role as a ceRNA of other miRNAs.…”
Section: Discussionmentioning
confidence: 92%